Peranan Kantor Perpustakaan, Arsip dan Dokumentasi dalam Peningkatan Pelayanan bagi Masyarakat - Lindawati Lindawati; Adelita Lubis (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2016)
This research was conducted at the office of the Library, Archives and Documentation Deli Serdang regency, which is located at Jalan Mawar office complex Regent of Deli Serdang. The choice of location or object of research is done deliberately with some specific considerations. One consideration is the location chosen was because of the lack of services provided personnel (employees) in the Office of Libraries, Archives and Documentation Deli Serdang that concern for the public interest is reduced. Issues raised in this research are: (1) Lack of library services resulted in low interest of the public to visit the Library, Archives and Documentation Deli Serdang, (2) lack of understanding of library employees, Archives and Documentation Deli Serdang on excellent service, (3) Not a good implementation of the excellent service at the office of the Library, Archives and Documentation Deli Serdang. This study used a qualitative research method, which is used in a study to obtain a qualitatively and will be largely dominated by the words, sentences and descriptions as well as rarely using numerical data, although did not rule out the display tables or graphs to support the completeness of the data.